VISITORS PERCEPTION ABOUT THE SAPTA PESONA IMPLEMENTATION IN KAMPUNG FLORY SLEMAN YOGYAKARTA - Septio, Achmad; Karyani, Tuti; Djuwendah, Endah (Journal of Business on Hospitality and Tourism, 2019)
Sapta pesona is a condition who expected to be able to create a comfortable and give a good impression to every visitor who comes. Kampung Flory is one of the agro-tourism located in Sleman Regency, Special Region of Yogyakarta, which began popular since 2016. The potential offered is quite diverse, ranging from nature tourism, outbound, to culinary with a distinctive nuance. Visitors who come tend not to increase even on certain days it looks very quiet. Based on visitor’s data from January to July 2019, there was a decrease from January to April 2019. This study aims to determine visitors' perceptions about the implementation of sapta pesona in Kampung Flory. The method used is qualitative with a case study. The results showed that the implementation of sapta pesona in Kampung Flory was good, but there were still some things that needed to be improved especially joglo souvenirs as aspects of the memory attribute.